Region Adaptive R- λ Model-Based Rate Control for Depth Maps Coding - Lei, Jianjun; He, Xiaoxu; Yuan, Hui; Wu, Feng; Ling, Nam; Hou, Chunping (IEEE transactions on circuits and systems for video technology, 2018)
In this paper, a novel rate-control algorithm based on the region adaptive R- λ model is proposed for depth maps coding. First, in order to obtain an accurate rate control for depth maps coding, a modified frame level bit allocation method based on coding bits statistical distribution of depth maps is proposed. Second, considering that different areas in a depth map have an imparity effect on virtual view rendering, the blocks of the depth map are divided into two types, namely, interested blocks for virtual view rending (IBV) and noninterested blocks for virtual view rending (NIBV). Then, two different R- λ models are derived for IBV and NIBV, respectively. The optimal bitrates for IBV and NIBV are determined by solving an optimization problem. After that, based on the regional R- λ models, the optimal Lagrange multipliers are calculated for both IBV and NIBV. Finally, the largest coding unit (LCU) level rate control is performed by adaptively adjusting the Lagrange multiplier to avoid blocking artifacts and smooth the quality of coding. Experimental results demonstrate that the proposed method can achieve considerable BD-PSNR gains compared with the unified rate-quantization model and conventional R- λ model-based algorithms in terms of rendered virtual views quality.